High-cycle fatigue and surface layer stability of case-hardened PM-steels with graded porosity. (8th August 2021) - Damon, James M.; Jung, Erik; Zürn, Michael; Dietrich, Stefan; Schulze, Volker
ABSTRACT: In order to increase the fatigue performance of mechanically loaded PM-components, case hardening procedures can be used to improve the surface layer states in terms of hardness and residual stress. In this work, the effects of carbonitriding treatment on two typical PM-steels with multiple densities are investigated in terms of their surface layer state (hardness, residual stress and retained austenite) before and after fatigue testing and their resulting pulsating fatigue performance. The results confirm fatigue strengths that can be formulated linearly as a function of porosity as well as a cyclic stability of the surface layer condition at loads below the fatigue strength. Further optimisation of the fatigue strength can be expected by tailoring the surface layer with respect to residual stresses. Comparisons to other studies are difficult due to many process parameters, different load cases and limited data, but indicate comparable fatigue strengths.